THE RELATIONSHIP OF MOTHER'S KNOWLEDGE WITH INCREASED WEIGHT OF BABIES AGED 3-6 MONTHS IN THE WORK AREA OF BANDAR MASILAM PUSKESMAS, SIMALUNGUN REGENCY, NORTH SUMATRA IN 2021 - Srimis Leini Saragih (Science Midwifery, 2022)
Infancy starts from the age of 0-12 months which is characterized by rapid growth and physical changes accompanied by changes in nutritional needs. The weight growth of infants aged 0-6 months has increased by 150 -210 grams / week. Lack of knowledge of the mother affects the rate of growth of the baby's weight which can result in the baby being malnourished during its growth period. Descriptive survey research method uses a descriptive correlational design. The population in this study were all mothers who had babies aged 3-6 months, the sampling technique was accidental sampling with a total of 50 respondents. The instrument used in the form of a questionnaire. Data analysis using the Chi-Square Test. Based on the results of the study, the majority of 50 respondents had sufficient knowledge as much as 31 (62%). The Chi Square test result is 0, 013 it can be seen that the calculation of the significant coefficient test is obtained at the real initials a = 0.05 and the Chi Square test p = 0.013 so that 0.013 <0.05. Based on the results of the study, it was concluded that there was a significant relationship between mother's knowledge and weight gain of babies aged 3-6 months in the Simpang Dolok Health Center Work Area, Limapuluh District, Batubara Regency. and pay attention to the baby's eating pattern and baby's sleep pattern.